Altered knee kinematics after posterior cruciate ligament single-bundle reconstruction—a comprehensive prospective biomechanical in vivo analysis - Oehme, Stephan; Moewis, Philippe; Boeth, Heide; Bartek, Benjamin; von Tycowicz, Christoph; Ehrig, Rainald; Duda, Georg N.; Jung, Tobias (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: Passive tibiofemoral anterior-posterior (AP) laxity has been extensively investigated after posterior cruciate ligament (PCL) single-bundle reconstruction. However, the PCL also plays an important role in providing rotational stability in the knee. Little is known in relation to the effects of PCL single-bundle reconstruction on passive tibiofemoral rotational laxity. Gait biomechanics after PCL reconstruction are even less understood. The aim of this study was a comprehensive prospective biomechanical in vivo analysis of the effect of PCL single-bundle reconstruction on passive tibiofemoral rotational laxity, passive anterior-posterior laxity, and gait pattern. Methods: Eight patients undergoing PCL single-bundle reconstruction (seven male, one female, mean age 35.6 ± 6.6 year, BMI 28.0 ± 3.6 kg/m²) were analyzed preoperatively and six months postoperatively. Three of the eight patients received additional posterolateral corner (PLC) reconstruction. Conventional stress radiography was used to evaluate passive translational tibiofemoral laxity. A previously established rotometer device with a C-arm fluoroscope was used to assess passive tibiofemoral rotational laxity. Functional gait analysis was used to examine knee kinematics during level walking. Results: The mean side-to-side difference (SSD) in passive posterior translation was significantly reduced postoperatively (12.1 ± 4.4 mm vs. 4.3 ± 1.8 mm; p < 0.01). A significant reduction in passive tibiofemoral rotational laxity at 90° knee flexion was observed postoperatively (27.8 ± 7.0° vs. 19.9 ± 7.5°; p = 0.02). The range of AP tibiofemoral motion during level walking was significantly reduced in the reconstructed knees when compared to the contralateral knees at six-month follow-up (16.6 ± 2.4 mm vs. 13.5 ± 1.6 mm; p < 0.01). Conclusion: PCL single-bundle reconstruction with optional PLC reconstruction reduces increased passive tibiofemoral translational and rotational laxity in PCL insufficient knees. However, increased passive tibiofemoral translational laxity could not be fully restored and patients showed altered knee kinematics with a significantly reduced range of tibiofemoral AP translation during level walking at six-month follow-up. The findings of this study indicate a remaining lack of restoration of biomechanics after PCL single-bundle reconstruction in the active and passive state, which could be a possible cause for joint degeneration after PCL single-bundle reconstruction.